New Insights and Methods in the Approach to Thalassemia Major: The Lesson From the Case of Adrenal Insufficiency - Poggi, Maurizio; Samperi, Irene; Mattia, Lorenza; Di Rocco, Arianna; Iorio, Cristina; Monti, Salvatore; Pugliese, Giuseppe; Toscano, Vincenzo (Frontiers in Molecular Biosciences, 2020)
Thalassemia Major (TM) is a complex pathology that needs a highly skilled approach. Endocrine comorbidities are nowadays the most important complications, including hypogonadism, hypothyroidism, diabetes mellitus and bone diseases. Recent works stated that in TM could be present a relevant prevalence of adrenal insufficiency (AI) and this fact may become crucial, especially in case of major stressful events. Aim: Test the reliability of standard test to diagnose AI in a group of TM and correlate it with clinical, haematological and radiological data. Methods: We evaluated endocrine damages and the efficacy of iron chelation therapy in 102 patients affected by TM. AI was assessed by tetracosactide (Synacthen) 1 mcg iv (low-dose test, LDT) stimulation test. Patients with a subnormal response (peak cortisol < 500 nmol/L) were followed up to 5 years to check symptoms and signs of AI. Results: We found AI in the 13.7% of the population studied. We did not find any correlation between AI and all data evaluated. Only female gender seems to be a protective factor. Follow up of the patients affected by AI showed no signs of adrenal crisis, in spite of no replacement therapy. Conclusions: Our study shows a relevant prevalence of AI in TM, especially males. The absence of adrenal crisis, in spite of no replacement therapy, during the long-term follow up, seems to underline that current methods to evaluate AI, in TM, should consider different and specific diagnostic test or different cut off for diagnosis.